2017
DOI: 10.1007/s00276-016-1811-x
|View full text |Cite|
|
Sign up to set email alerts
|

Anatomical basis of the extended TDAP flap: study of its territories of vascularization and its volume

Abstract: The thoracodorsal artery perforator via the deep muscular fascial network allows us to harvest a flap of 25 cm × 20 cm with a mean surface of 441 cm² and a mean volume of 193 ml. The extended TDAP flap is a credible option in breast reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…16 The most important factor in flap surgery is the main pedicle of the flap; thus, an accurate knowledge of vascular anatomy is very important and fundamental in flap surgery. 17 The LD flap is a fan-shaped flap that offers the advantages of providing a muscle rich in blood supply, providing a bulky flap no matter the defect, and causing little problem in the activities of daily living due to few donor site complications. 18,19 Owing to such advantages, it is a flap used not only in breast reconstruction, but also in the reconstruction of large and complex tissue defects in the maxillofacial region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 The most important factor in flap surgery is the main pedicle of the flap; thus, an accurate knowledge of vascular anatomy is very important and fundamental in flap surgery. 17 The LD flap is a fan-shaped flap that offers the advantages of providing a muscle rich in blood supply, providing a bulky flap no matter the defect, and causing little problem in the activities of daily living due to few donor site complications. 18,19 Owing to such advantages, it is a flap used not only in breast reconstruction, but also in the reconstruction of large and complex tissue defects in the maxillofacial region.…”
Section: Discussionmentioning
confidence: 99%
“…16 The most important factor in flap surgery is the main pedicle of the flap; thus, an accurate knowledge of vascular anatomy is very important and fundamental in flap surgery. 17…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 36 , 37 In 2015, Gunnarsson et al 38 and Angrigiani et al 39 described the extended version of the TDAP flap, which included additional fat tissue on each side of the skin paddle to allow for a more voluminous flap. Dast et al, 36 in a recent anatomical study, reported that the TDAP flap via the deep muscular fascial network allows for a harvest flap with a mean surface of 441 cm 2 and a mean volume of 193 g. In select cases, the TDAP flap can also achieve total breast reconstruction alone or in combination with fat grafting. 19 In our review, partial breast defects varied from lumpectomy to outer columnar mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the vascular territory of TDA perforators includes adipose tissue beyond the lateral border of the LD muscle, and free adipose flaps that use TDA septocutaneous perforators have been reported. 14 , 15 In the present study, we avoided skeletonizing the performing vessels in adipose flap during surgery, and efforts were made to preserve the network of blood vessels between the tissues by elevating the adipose flap and LD muscle as a single unit (Figs. 1 and 2 ).…”
Section: Methodsmentioning
confidence: 99%